Identification of Subsidence Type and Potential Based on Geological and Geoelectrical Data in Bedoyo and Surrounding Areas, Kab. Gunung Kidul, Yogyakarta - Waskita, Waskita Murti Bambang Yudhana; Wanengcio Uligawati, Garnis; Pitaloka, Mayang; Rizqi, Al Hussein Flowers (ReTII, 2021)
Gunung Kidul Regency, especially Ponjong District, in the period until 2019 there has been subsidence in several villages with different location points.The sinkhole that occurs has varying hole diameters and depths. The research method used is the surface geology method and the subsurface method which includes observations of morphology, rock and geological structures and subsurface including geoelectric data collection of the Schlumberger configuration. Based on the results of the occurrence of subsidence in the research area, there is a conclusion that in Bedoyo Village and its surroundings there are 2 types of subsidence, namely dropout sinkhole and suffosion sinkhole. The results of the analysis of surface and subsurface geological data show that there are 3 subsidence hazard zones in the study area, namely the vulnerable zone (55%), medium zone (38%), and low zone (7%).